Exploring mobile 4G adoption in Malaysia - Zendehdel, Marzieh; Paim, Laily; Delafrooz, Narges (Research Academy of Social Sciences, 2015)
The purpose of this paper is to determine the main factors affecting mobile 4 G service for adoption. The main reason to stimulate the present study was the significantly low rate of using 4G service among mobile users in Malaysia where unlike many other countries the rate of this usage runs in opposite way. Thanks to increasing advances in wireless communications devices, the number of mobile users has growingly increased and as a result the development of mobile commerce (m-commerce) has been accelerated. The research attempts to examine the factors predicting consumer intention for m-4 G adoption in Malaysia. For the purpose of the research, the diffusion of innovation model and some other variables are integrated including awareness, affordability, accessibility and acceptability. The research findings revealed that in view of consumers, acceptability, accessibility, affordability seem more significant than awareness in regard with 4G adoption. Identifying the above factors will drive telecom operators to provide more successful 4G services to enhance the rate of 4G service adoption.